Measurement Methods Effects on the Swithing Behaviour of Sputtered Titania Thin Films - Sadeghikia, Fatemeh; K. Horestani, Ali; T. Noghani, Mahmoud; Reza Dorbin, Mohammad; Mahdikia, Hamed; Ja'afar, Hajar (International Journal of Engineering and Technology, 2018)
The aim of this study is to examine the effect of the tube radius in a cylindrical plasma antenna on the radiation efficiency of the antenna and on some of the physical characteristics of the plasma. It is shown that density of the plasma at the excitation point and also the height of the column varies proportionally to the square root of the ratio of the inner radius to the outer one, provided the length of the tube is longer than the height of the excited plasma. Plasma density and antenna height in the column with a smaller radius derived by the analytical approach lead to a more efficient antenna in a lower working frequency and narrower bandwidth.Â Â